Posttranslational modifications as therapeutic targets for intestinal disorders. (March 2021) - Choo, Jieun; Heo, Gwangbeom; Pothoulakis, Charalabos; Im, Eunok
Graphical abstract: Abstract: A variety of biological processes are regulated by posttranslational modifications. Posttranslational modifications including phosphorylation, ubiquitination, glycosylation, and proteolytic cleavage, control diverse physiological functions in the gastrointestinal tract. Therefore, a better understanding of their implications in intestinal diseases, including inflammatory bowel disease, irritable bowel syndrome, celiac disease, and colorectal cancer would provide a basis for the identification of novel biomarkers as well as attractive therapeutic targets. Posttranslational modifications can be common denominators, as well as distinct biomarkers, characterizing pathological differences of various intestinal diseases. This review provides experimental evidence that identifies changes in posttranslational modifications from patient samples, primary cells, or cell lines in intestinal disorders, and a summary of carefully selected information on the use of pharmacological modulators of protein modifications as therapeutic options.